Colorado secondary ensemble teachers' perceptions of the integration of students with disabilities - Gray, Samuel David, author; Johnson, Erik, advisor; Bacon, Joel, committee member; Lopes, Tobin, committee member (Colorado State University. Libraries, 2023)
Inclusive practices are required of K-12 educators regarding the inclusion and integration of students with special needs through the Individuals with Disabilities Act (1975) and the Every Student Succeeds Act (2015). However, barriers to integrating students with disabilities may exist in secondary performing ensembles. These barriers include paraprofessional staffing, educator efficacy, community stakeholder expectations, and educator professional development. Implementing and understanding these barriers is vital to providing secondary music educators with the proper tools to provide an integrated performing ensemble. While the inclusion of students with disabilities often occurs in a performing ensemble, the scope of integration may vary depending on educator decisions. When an educator faces this situation, understanding any decisional difference is needed. The purpose of this study is to investigate Colorado music educators' perceptions regarding the current practices of inclusion and integration of students with disabilities in Colorado's secondary public schools (middle or high schools). Furthermore, this study examines educators' perceptions regarding inclusive practices where students with disabilities are included in ensemble settings. This study can help inform discussions, methods, and policies related to the professional development of in-service educators and pre-service educator preparatory programs regarding the integration and inclusion of students with disabilities. In this study, the following research questions were asked: What is the level of concern and self-efficacy of Colorado secondary music educators about integrating students with disabilities? What is the relationship between years of teaching experience, concerns, and self-efficacy about the inclusion and integration of students with disabilities? Do Colorado secondary music teachers vary in their level of concern and teaching efficacy at various stages of their career or by school location? The adapted SACIE-R and TSES questionnaire included the concerns subset of the Sentiments, Attitudes, and Concerns about Inclusive Education – Revised Scale (Forlin et al., 2011) and the Teacher Self-Efficacy Scale (Tschannen-Moran & Hoy, 2001). Both scales utilized a four-point Likert scale. Data was compiled from mid-November through early mid-December of 2022. Findings from this preliminary investigation indicate that as educator experience increases, the level of educator concern about integrating students with disabilities decreases. Additional findings suggest no statistical significance between educator district setting and the level of concern and efficacy about students with disabilities.
Keywords: integration; students with disabilities; inclusion; teacher self-efficacy; secondary performing ensembles